Approaches of National Information and Science Policies in Turkey - Mehmet Toplu (Türk Kütüphaneciliği)
Science policy has an important role in the process of identification ofthe national information policy. While information offered through information services, systems and networks is the output of scientific research, again it is mostly used by individuals, organizations and institutions involved, in research. The ability to provide the information required in all walks of life, from the information created and accumulated nationally gives a direction to the. development of the information policy. Turkey has not got an information policy which has been produced by the contributions of all sectors involved,, from production of information to its usage, with a view of the requirements of each sector. Although not in the context of a policy, development of information services has been handled within the science and technology policies attempted to be identified. Views which rather focus on the utilization of information accumulated at international level, have not helped in the utilization of information accumulated at national level. In addition to this, science policy has not become functional. As a result national information creation has remained low. Consequently an information infrastructure dependent on informa tion sources produced outside the country has emerged.